Modern methods of intraoperative fluorescent imaging of the parathyroid glands in endocrine surgery: a literary review - S. V. Zinchenko; N. A. Shanazarov; N. F. Muratov; S. D. Kisikova; K. S. Seitbekova; I. Z. Galiev; M. I. Ibragim; R. R. Ahmetshin (Biomedical Photonics, 2025)
Hyperparathyroidism (primary, secondary and tertiary) is a common endocrine disease, often occurring with pronounced symptoms, in most cases caused by adenoma (rarely several adenomas) in primary hyperparathyroidism (pHPT) and chronic renal failure in patients on programmed hemodialysis with secondary (sHPT) and tertiary (tHPT) hyperparathyroidism. To date, the only radical treatment for hyperparathyroidism (HPT) is surgical removal of pathologically altered parathyroid glands. In this regard, there is a need to improve diagnostic search algorithms, including intraoperative ones, for altered parathyroid glands. The main objective of the review is to study current trends and techniques of intraoperative imaging of the parathyroid glands, compare these methods and evaluate their effectiveness. The use of qualitatively new technologies for the topical diagnosis of altered parathyroid glands, such as identification by autofluorescence in the near infrared spectrum (NIRAF), the technique of using indocyanine green (ICG) and 5-aminolevulinic acid under UV radiation, make it possible to visualize the localization of the parathyroid glands with more than 90% accuracy. However, the issue of their priority use remains open and unresolved.